2023
DOI: 10.20945/2359-4292-2022-0334
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of osteoporosis therapy with bisphosphonates

Bárbara Gehrke,
Maria Caroline Alves Coelho,
Catarina Brasil d'Alva
et al.

Abstract: Bisphosphonates (BPs) are medications widely used in clinical practice to treat osteoporosis and reduce fragility fractures. Its beneficial effects on bone tissue have been consolidated in the literature for the last decades. They have a high affinity for bone hydroxyapatite crystals, and most bisphosphonates remain on the bone surface for a long period of time. Benefits of long-term use of BPs: Large and important trials (Fracture Intervention Trial Long-term Extension and Health Outcomes and Reduced Incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Along with suppressed bone turnover, AFFs are known to be prone to nonunion. Because the femur is a weight-bearing bone and its nonunion may highly reduce a patient's ADLs, an early discontinuance of BMA treatment and the introduction of another drug such as teriparatide after surgical treatment are mandatory for the faster healing of AFFs [3,17]. Moreover, Tsuchie et al reported that the administration of teriparatide after the occurrence of the first AFF and the use of active vitamin D3 after the completion of teriparatide therapy may prevent the recurrence of AFF [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with suppressed bone turnover, AFFs are known to be prone to nonunion. Because the femur is a weight-bearing bone and its nonunion may highly reduce a patient's ADLs, an early discontinuance of BMA treatment and the introduction of another drug such as teriparatide after surgical treatment are mandatory for the faster healing of AFFs [3,17]. Moreover, Tsuchie et al reported that the administration of teriparatide after the occurrence of the first AFF and the use of active vitamin D3 after the completion of teriparatide therapy may prevent the recurrence of AFF [18].…”
Section: Discussionmentioning
confidence: 99%
“…With the background of the globally aging population and the high awareness of osteoporosis and osteoporosis-related fragility fractures [1], the number of individuals diagnosed with osteoporosis and requiring medical treatment is increasing. Bone-modifying agents (BMAs), including bisphosphonate and denosumab, are widely used to treat osteoporosis, but some severe potential side effects of long-term BMA treatment have emerged: osteonecrosis of the jaw and atypical fractures [1][2][3][4]. Most of the reported atypical fractures occurred in weight-bearing bones, and the femur is the most frequently affected weight-bearing bone (atypical femoral fracture; AFF) [2].…”
Section: Introductionmentioning
confidence: 99%